ANALISIS KOHERENSI PADA KITAB MORMON - TANGKAWAROUW, JAMES (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT The research is entitled Coherence in the Book of Mormon Chapter 1 to 9. It is an attempt to anlyze and explain the items of coherence. The objectives of this research is to identify, classify, and analyze the items of coherence in the Book of Mormon Chapter 1 to 9 The writer conducts this research by using descriptive method. The data were taken from the Book of Mormon chapter 1 to 9 and analyzed based on Juezâ€™ (2008). The findings show that there are 79 marked coherence ( 26 words of addition, 20 words of casuality, 2 words of condition, 24 words of instrument, 3 words of tempo, 4 words of intensity ) but there is no marked coherence on contrast, conclusion, comparison, similiar, and validitation. In addition unmarked coherence is not found in the data. Keywords : Discourse Analysis, The Book of Mormon., Coherence Items Â